Sustainability Marketing and Consumer Perception: A Case Study on Uniqlo Malaysia’s Green Transformation - Odebunmi Abayomi Tunde; Shweta Saxena; Nur Aleeya Binti Mohd Azhar; Nur Aishah Amaludin; Nur Aisyah Binti Manan; Nur Alia Asrina Binti Mohd Jefri; Aarti Chaudhary; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
This study examines the influence of sustainability marketing on consumer perception across Asia, focusing on UNIQLO Malaysia’s green transformation as a case study. The research aims to explore how Malaysian consumers respond to sustainable business practices such as ethical sourcing, recycling, and eco-friendly product design. This quantitative research uses an online survey distributed via Google Forms targeting consumers from Malaysia who are familiar with the UNIQLO brand. A non-probability sampling method, specifically the convenience sampling technique, will be applied to gather responses from 152 UNIQLO customers (N = 152) based on their availability and willingness to participate. The collected data will be analyzed using descriptive statistics and regression analysis in SPSS to determine the relationship between sustainability marketing and consumer attitudes, trust, and loyalty. The findings are expected to show the sustainable marketing strategies positively influence consumerperceptionandstrengthen brandimageintheretailindustry.The study concludes that integrating sustainablepracticesintomarketing strategies enhance brand image, strengthencustomerrelationships,and promote environmental responsibility.